Three-Dimensional Assessment of Vertebral Derotation in Adolescent Idiopathic Scoliosis: Review of a Surgical Technique and Its Success in Achieving Derotation in the Instrumented and Uninstrumented Spine. Issue 6 (5th June 2022) - Zuckerman, Scott L.; Segar, Anand H.; Cerpa, Meghan; Chanbour, Hani; Sardar, Zeeshan M.; Lenke, Lawrence G.
Abstract : BACKGROUND: Three-dimensional (3D) imaging represents a novel way to assess surgical derotation maneuvers in adolescent idiopathic scoliosis (AIS). OBJECTIVE: To assess the following in patients with AIS undergoing derotation surgery with Lenke type 1/2 curves using 3D imaging: (1) the primary outcome of thoracic apical vertebral rotation (T-AVR) and (2) secondary outcomes of thoracic kyphosis (TK), lumbar AVR (L-AVR), and rotation of each thoracic/lumbar vertebrae. METHODS: A retrospective, pilot study of type 1/2 AIS patients from 2017 to 2018 was performed. All patients received posterior pedicle screw/rod constructs with consistent direct vertebral derotational maneuvers and received full length SterEOS imaging with 3D reconstruction. The primary outcome of interest was T-AVR. Secondary outcomes included TK, L-AVR, and rotation at each thoracic/lumbar vertebrae. RESULTS: Fifteen patients (mean age 15.7 ± 1.2 years, 67.0% female) were studied. The mean preoperative/postoperative Cobb angle of the major curve was 51.8° ± 14.9° (range 39.8-62.0) and 11.0° ± 5.1° (range 3.7-20.7). Mean level fused was 10.5 ± 1.2. The primary outcome of T-AVR showed significant improvement (13.8° ± 12.5° vs 9.2° ± 8.6°, P = .015) after surgery, along with secondary outcome of TK (T1-12/T4-12, P = .008/.027). Significant spontaneous rotational improvement was seen in L-AVR ( P = .016). Significant improvement was also seen in 11 of 17 (64.7%) individual vertebrae (T3-8/T11-L3) ( P < .05). CONCLUSION: In Lenke Type 1/2 AIS patients undergoing surgical derotation and fusion, 3D imaging techniques captured improvements in rotation. Significant postoperative improvement was seen in T-AVR, TK, L-AVR, and rotation of the individual vertebrae T3-8/T11-L3. These pilot results warrant the study of 3D imaging in all patients with AIS and other scoliosis populations.